Optimization model with nonlinear programming and Monte Carlo simulation of an industrial fishing project - Ramos Angeles, Christian (2019)
The present research work consists in the development of a method where a mathematical model of a fish canning plant installation project is proposed, considering the investment, the production costs, the operating expenses, the financial statements, and as indicators for decision making, the net financial present value and internal rate of financial return. Then, the mathematical model is optimized using a non-linear programming to choose the most convenient investment alternative, then a Monte Carlo simulation is carried out in which random variables of plant and market are considered that allow the investor to estimate the minimum values and máximum that can happen in the financial indicators and finally the discussion of results.